Treatment of Candiduria with Micafungin: A Case Series - Danny Lagrotteria; Coleman Rotstein; Christine H Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
There has been a gradual increase in the incidence of non-Candida albicans-related nosocomial infections. Candida glabrata urinary tract infections have increased in frequency, and treating these infections can be difficult because the organism may be resistant to fluconazole. A newer antifungal agent, micafungin, which belongs in the class of echinocandins, provides an alternative and effective therapy against C glabrata. The present report describes three cases of C glabrata-associated urinary tract infections successfully treated with micafungin. To the authors’ knowledge, this is the first report of successful treatment of C glabrata and azole-resistant C albicans-associated urinary tract infection with an echinocandin.